2007
DOI: 10.1111/j.1550-7408.2007.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Description of Deviata rositae n. sp., a New Ciliate Species (Ciliophora, Stichotrichia) from Argentina

Abstract: Soil samples were taken from a temporary pond located in Buenos Aires province, Argentina, during the dry phase in the summer of 2005. The ciliates were studied alive and after staining with protargol. Deviata rositae n. sp. measures 112-154 microm in length and 21-28 microm in width in vivo and has a vermiform body. The contractile vacuole is located in the mid-body on the left. The macronucleus is moniliform and there are 1-3 micronuclei. The oral apparatus is composed of 14-18 adoral membranelles and straig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…nov.). KÜPPERS et al (2007) reported barren kinetids in ventral surface of D. rositae and in a population preliminarily identified as Deviata cf. bacilliformis.…”
Section: Remarksmentioning
confidence: 99%
“…nov.). KÜPPERS et al (2007) reported barren kinetids in ventral surface of D. rositae and in a population preliminarily identified as Deviata cf. bacilliformis.…”
Section: Remarksmentioning
confidence: 99%
“…Compared with our form, the original population is smaller (112–154 × 21–28 μm in vivo and 98–154 × 25–56 μm after protargol impregnation vs. 200–300 × 15–25 μm in vivo and 140–267 × 23–60 μm after protargol impregnation) and has a little more macronuclear segments (7–14, 9 on average, vs. 4–8, 6 on average) and fewer cirri (Küppers et al. ). However, these differences can be considered as population‐dependent, owing to the variation of body size of limnetic and terrestrial ciliates (Foissner et al.…”
Section: Discussionmentioning
confidence: 53%
“…Our population possesses most of the diagnostic features described by Küppers et al. (), especially only two long frontoventral rows as well as one long and one short dorsal kinety. Compared with our form, the original population is smaller (112–154 × 21–28 μm in vivo and 98–154 × 25–56 μm after protargol impregnation vs. 200–300 × 15–25 μm in vivo and 140–267 × 23–60 μm after protargol impregnation) and has a little more macronuclear segments (7–14, 9 on average, vs. 4–8, 6 on average) and fewer cirri (Küppers et al.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations